(untitled) (Journal of Economic Research & Business Administration, 2015)
The article discusses the relationship between quality management and branding at the University. The brand of the University is on the one hand, one factor that unites the main indicators of the quality of the University, on the other hand is a powerful tool for promoting the University and its services on the market. Therefore, it is proposed to create a «brand» wheel for each group of users. On the basis of the value of the brand has been developed and proposed criteria for introduction of quality management system model of education in the University, focused on the international ranking. Such an approach at a glance authors will have the desired impact on the changing attitudes of consumers, by bringing to them the relevant information. Strengthen the impact of use of complex marketing communications.